2021
DOI: 10.3390/polym13244390
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Porous Scaffolds Derived from Bovine Cancellous Bone Matrix Promote Osteoinduction, Osteoconduction, and Osteogenesis

Abstract: The use of three-dimensional porous scaffolds derived from decellularized extracellular matrix (ECM) is increasing for functional repair and regeneration of injured bone tissue. Because these scaffolds retain their native structures and bioactive molecules, in addition to showing low immunogenicity and good biodegradability, they can promote tissue repair and regeneration. Nonetheless, imitating these features in synthetic materials represents a challenging task. Furthermore, due to the complexity of bone tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Similarly, other studies indicated that the size of porosity on the CaP surface (<50 µm) is considered as micropores [14,15]. Moreover, a previous study proposed that the osteoconductive properties of powder ceramics can be improved by increasing the microporosity [16,17]. Furthermore, researchers showed that the micropores can enhance the local mechanical properties of powders.…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, other studies indicated that the size of porosity on the CaP surface (<50 µm) is considered as micropores [14,15]. Moreover, a previous study proposed that the osteoconductive properties of powder ceramics can be improved by increasing the microporosity [16,17]. Furthermore, researchers showed that the micropores can enhance the local mechanical properties of powders.…”
Section: Discussionmentioning
confidence: 91%
“…Physical, chemical, mechanical, or electrical signals [8,9]. The interaction between the mentioned elements is directly related to the chemical and topographic characteristics of the scaffold (similar to the extracellular matrix), which will act as a physical layer for cell development and differentiation [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, osteoconduction is the property that allows the bone to grow on the surface of the bone substitute material (BSM) or to grow downward into the voids or channels of the material ( Weber, 2019 ). In bone healing, the extracellular matrix (ECM) component that exerts an osteoconductive role allows differentiated osteoblasts to adhere, migrate, and proliferate at the site of injury while its interconnected voids facilitate adequate blood vessel formation ( Malagon-Escandon et al, 2021 ). Mesenchymal stem cells (MSCs) present in bone and its surrounding tissues that are essential for bone healing or implant fixation, but are less differentiated, can be recruited to form bone progenitor cells and develop into differentiated osteoblasts over time with appropriate stimulation (common inducing agents, such as growth factors), which is a process known as osteoinduction ( Albrektsson and Johansson, 2001 ; Vermeulen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%